Photovoltaic-integrated review and expansion need in green building landscape for bridging the malaysian RE policy - Mohd Effendi Amran; Mohd Nabil Muhtazaruddin; Nurul Aini Bani; Sharipah Alwiah Syed Abd Rahaman; Nelidya Md Yusoff; Mohd Hanapi Azizul; Firdaus Muhammad-Sukki (Institute of Advanced Engineering and Science, 2020)
A literature review is presented specifically on the photovoltaic (PV) as a distributed generation (DG) integration approach and the extensiveness through renewable energy (RE) assessment criteria in current green building rating system (GBRS) to: delineate for further classification in terms of installed-capacity; identify the RE applications’ intent / aim; and recommendation for PV-type DG (PV-DG) expansion needs. The paper aims to close the gap in knowledge, by an empirical review of current RE assessment criteria and to portray the expected evolution of RE for higher installed-capacity in ensuring the government key achievement can be achieved. In considering the expansion needs in GBRS, the optimal technique for PV-DG expansion-limit would serve as a conceptual bridge between expanding mechanism and realization of the Malaysian most recent RE policy specifically on the drastically increment of RE quota. These can be achieved since various DG optimization case studies have been presented and overcome with the improvement impact on the test system, in term of power loss reduction, increased efficiency and optimal cost outcome. Future analysis as well as research direction are proposed and linked with some of the previous optimization reviews in recent literature.